(untitled) (Journal of Information Technology and Digital World, 2024)
The research is designed to help new students entering campus by offering them skill development opportunities right from the start of their academic journey. The research provides a platform where students can choose a specific skill domain to improve upon. It also offers a personalized learning paths for them, packed with various resources. Additionally, a continuous assessment through tests, AI chat bot support, personalized student logins, and faculty admin access for efficient management is also offered. The goal of the research is to support students in enhancing their skills and succeeding academically.